2017
DOI: 10.1111/ene.13340
|View full text |Cite
|
Sign up to set email alerts
|

Netrin‐1 and multiple sclerosis: a new biomarker for neuroinflammation?

Abstract: Netrin-1 decreased in EAE and in MS patients, mainly during relapse, suggesting an anti-inflammatory role of netrin-1. Further research should be performed in a larger cohort of patients to validate netrin-1 as a biomarker of MS inflammatory activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…Furthermore, neutralization of UNC5B receptor‐induced monocyte and neutrophil infiltration thus increased kidney injury . In line with these results, obese patients and patients with multiple sclerosis showed significantly lower circulating Netrin‐1 levels than those of controls. Liu, et al reported that plasma Netrin‐1 levels were lower in newly diagnosed type 2 diabetes mellitus patients than those in healthy controls and also the levels were negatively correlated with blood glucose levels and insulin resistance.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, neutralization of UNC5B receptor‐induced monocyte and neutrophil infiltration thus increased kidney injury . In line with these results, obese patients and patients with multiple sclerosis showed significantly lower circulating Netrin‐1 levels than those of controls. Liu, et al reported that plasma Netrin‐1 levels were lower in newly diagnosed type 2 diabetes mellitus patients than those in healthy controls and also the levels were negatively correlated with blood glucose levels and insulin resistance.…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, neutralization of UNC5B receptor-induced monocyte and neutrophil infiltration thus increased kidney injury. 12 In line with these results, obese patients 15 and patients with multiple sclerosis 30 showed significantly lower circulating Netrin-1 levels than those of controls. Liu, et al 31 reported…”
Section: Discussionsupporting
confidence: 65%
“…In the present study, TNFα, a proinflammatory marker has been shown to increase in RR-multiple sclerosis [75,76] and to be consistently elevated regardless of the status of disease type (i.e., clinically isolated syndrome, primary progressive, or relapsing-remitting), with serum levels 40-50% higher in multiple sclerosis subjects relative to controls. Preclinical studies have reported an association between TNFα and impaired memory in mice with EAE [77] and implicated astrocyte signaling as the downstream target of overexpression of the cytokine.…”
Section: Discussion and Summarysupporting
confidence: 52%
“…The management and outcome of multiple sclerosis has been transformed by the use of immunomodulation therapies . Outcome measures, as judged by patient‐reported outcomes, remain an important area for development and are relevant for care delivery design .…”
mentioning
confidence: 99%
“…Outcome measures, as judged by patient‐reported outcomes, remain an important area for development and are relevant for care delivery design . The use of biomarkers that reflect natural history and response to treatment is invaluable and the use of cerebrospinal fluid neurofilament light protein and tau to correlate with brain atrophy is helpful . A provisional retrospective analysis has suggested that immunomodulatory therapy may not need to be continued indefinitely, but this needs to be the subject of further study .…”
mentioning
confidence: 99%